TEACHER EFFECTIVENESS OF HIGH SCHOOL TEACHERS IN RELATION TO SOME DEMOGRAPHIC VARIABLES - Dr. Sheikh Aabid Azad, Dr. sheeraz Ayoub Kuchy (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2021)
The present investigation has been under taken in order to study the teacher effectiveness of high school teachers in Anantnag District of Jammu and Kashmir. Teacher Effectiveness of high school teachers’ scale was constructed and standardized by Sujata Mishra (1999) has been administrated to a random sample of 400 high school teachers. It is found that teachers significantly differ in teacher effectiveness in respect of Gender, Marital Status, Type of School, Teaching Experience and they do not differ in teacher effectiveness in respect of Locality of School. It is found that teachers significantly differ in job involvement in respect of Gender, and Teaching Experience and they do not differ in job involvement in respect of Marital Status, Type of school, Locality of School. KEYWORDS: teacher effectiveness, descriptive survey method, random sampling, gender, marital status, Locality of school, Type of School, Teaching Experience.